The Resilience of Muslim Converts in Understanding Islam: the Role of al-Akbar Mosque for Post-Conversion Accompaniment - Wiwik Setiyani; Muktafi Muktafi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2020)
This article describes the way Muslim converts think and understand Islam after their conversion and how they pursue a moderate Islam in the post-conversion accompaniment provided by the al-Akbar mosque, Surabaya. The converts gain various Islamic knowledge as their initial foundation to know Islam. Since each of the Muslim converts has various interests in Islam, which might come from either internal or external factors, the post-conversion accompaniment provided by al-Akbar mosque has greatly helped converts’ lives. The finding shows that Muslim converts have found resilience in controlling their emotions, a sense of optimism after converting to Islam. Al-Akbar mosque was chosen as the place for pronouncing the faith and for studying the religion since many believe that the mosque provides direction and technical guidance on how to embrace Islam righteously. Moderate Islam is the motto of the al-Akbar mosque, which teaches tolerance by respecting views or thought about Islam. This knowledge strengthens their resilience and intensifies their faith to comprehend Islam consistently and to engender a strong generation committed to maintaining Islamic spiritual values. Keywords: Moderat Islam, mosque, Muslim convert.